Interferon- and ribavirin-free therapy with new direct acting antivirals (DAA) for chronic hepatitis C improves vascular endothelial function. (15th November 2018) - Schmidt, Frank P.; Zimmermann, Tim; Wenz, Till; Schnorbus, Boris; Ostad, Mir Abolfazl; Feist, Christina; Grambihler, Annette; Schattenberg, Jörn M.; Sprinzl, Martin F.; Münzel, Thomas; Galle, Peter R.
Abstract: Introduction: Chronic Hepatitis C virus infection (HCV) is associated with extrahepatic manifestations and an increased prevalence in cardiovascular disease. New direct acting antivirals (DAA) have revolutionized HCV treatment with high rates of sustained virological response (SVR). Recently it was demonstrated, that SVR reduces morbidity and overall mortality more than can be solely explained by hepatic effects, suggesting that treatment with DAA also affects cardiovascular disease. The aim of this pilot study was to identify possible underlying mechanisms behind the HCV-associated cardiovascular mortality reported by others. Methods and results: 20 HCV patients (10 genotype GT1, 10 GT3) were treated with interferon (IFN)- and ribavirin (RBV)-free DAA regimens for 12 weeks (SVR12). Primary endpoint was an improvement in endothelial function (flow-mediated dilation, FMD) at SVR12 compared to baseline. Patient demographics, FMD, markers for endothelial function and inflammation, coagulation and oxidative stress were measured at baseline, end of treatment and SVR12. All patients achieved SVR12. There was a significant increase in FMD from 9.4 ± 5.2% at baseline to 11.9 ± 4.5% at SVR12 (p = 0.04). Concomitantly, there were significant reductions in levels of endothelium-derived adhesion molecules E-selectin, VCAM-1 and ICAM-1. While APRI values were also significantly lower, liver stiffness did not change significantly. There were no relevant changes in systemic inflammation, oxidative stress, insulin resistance or coagulation pathways. Conclusions: Successful DAA therapy was associated with improvements in endothelial function and a reduction of soluble adhesion molecules. Our findings indicate that HCV infection affects the endothelium and that DAA-treatment reverses these effects and enhances endothelial function. Highlights: Chronic Hepatitis C virus infection (HCV) is associated increased prevalence in cardiovascular disease DAA reduce levels of endothelium-derived adhesion molecules E-selection, VCAM-1 and ICAM-1. DAA improve endothelial function in patients with chronic HCV infection. Our findings indicate that HCV infection affects the endothelium and that DAA-treatment reverses these effects.